2007
DOI: 10.1007/s00114-007-0236-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel concept of Fe-mineral-based magnetoreception: histological and physicochemical data from the upper beak of homing pigeons

Abstract: Animals make use of the Earth's magnetic field for navigation and regulation of vegetative functions; however, the anatomical and physiological basis for the magnetic sense has not been elucidated yet. Our recent results from histology and X-ray analyses support the hypothesis that delicate iron-containing structures in the skin of the upper beak of homing pigeons might serve as a biological magnetometer. Histology has revealed various iron sites within dendrites of the trigeminal nerve, their arrangement alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
182
3
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(197 citation statements)
references
References 45 publications
8
182
3
4
Order By: Relevance
“…Therefore, our findings suggest that the ophthalmic branch of the trigeminal nerve (V1) is the only trigeminal branch to mediate the effects of the magnetic stimuli that were observed in PrV and SpV and that the "extra" labeling outside the primary V1 terminal zone probably represents magnetic activation via a multisynaptic mechanism. These results are entirely consistent with previous anatomical studies, which have shown that the ophthalmic branch of the trigeminal nerve (V1) is the only branch to innervate candidate ferromagnetic structures in the upper beak (8,13). It is almost certain that magnetic information is transmitted to higher brain centers.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, our findings suggest that the ophthalmic branch of the trigeminal nerve (V1) is the only trigeminal branch to mediate the effects of the magnetic stimuli that were observed in PrV and SpV and that the "extra" labeling outside the primary V1 terminal zone probably represents magnetic activation via a multisynaptic mechanism. These results are entirely consistent with previous anatomical studies, which have shown that the ophthalmic branch of the trigeminal nerve (V1) is the only branch to innervate candidate ferromagnetic structures in the upper beak (8,13). It is almost certain that magnetic information is transmitted to higher brain centers.…”
Section: Discussionsupporting
confidence: 92%
“…More direct methods, such as electrophysiological recordings from trigeminal neurons in response to magnetic stimulation, would be required to prove this; however, as pointed out earlier here, such methods are very prone to the production of artifactual results (22-24); hence, the necessity for the present, strongly indicative study using more indirect methods. The data also suggest that the ophthalmic branch of the trigeminal nerve (V1) in European robins innervates a primary magnetic sensor in the upper beak and support the idea that iron-mineral-based structures found in the upper beak of birds (8,12,13) including European robins (15), can sense information from the ambient geomagnetic field.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We can only speculate about the physiological mechanisms of the magnetic alignment of ruminants. Of the numerous mechanisms proposed for the direct interaction of electromagnetic fields with the human or animal body, 3 stand out as operating potentially (also) at lower field levels: magnetically sensitive radical pair reactions (19), electric field ion cyclotron resonance interactions (20), and mechanisms based on biogenic magnetite (21)(22)(23)(24). Theoretically, each of these mechanisms (separately or in combination) could be responsible for magnetic alignment.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout, the focus is firmly on the primary reception mechanism: We make no significant attempt to review the behavioral studies that led to and have since supported the radical pair model, or to comment on (neuro)-physiological aspects of magnetoreception, all of which have been covered authoritatively and extensively in recent reviews (3-5, 8, 24, 25). Nor do we presume here to debate the relative merits of the radical pair hypothesis versus proposals based on biogenic magnetite (Fe 3 O 4 ) (26)(27)(28)(29)(30)(31)(32). We close with a discussion of cryptochrome, the photoreceptor protein that is presently the only molecule under consideration as the magnetoreceptor (2), and make suggestions for further research.…”
mentioning
confidence: 97%